Protective Effect of an Edible Tomato Plant Extract/Chitosan Coating on the Quality and Shelf Life of Sierra Fish Fillets - H. E. Ramírez-Guerra; F. J. Castillo-Yañez; E. A. Montaño-Cota; S. Ruíz-Cruz; E. Márquez-Ríos; D. F. Canizales-Rodríguez; W. Torres-Arreola; N. Montoya-Camacho; V. M. Ocaño-Higuera (Journal of Chemistry)
The products of fishing are highly perishable foods. Thus, it is necessary to seek viable alternatives that help to preserve product freshness and quality and to increase its shelf life. One of these alternatives is the use of extracts with antimicrobial activity obtained from plants, such as tomato, which has been observed to present compounds with antimicrobial activity. The objective of this work was to determine the effect of an extract obtained from the tomato plant and incorporated into an edible chitosan coating on the quality and shelf life of the sierra fish fillet stored on ice for 15 days. For the latter, an extract was prepared with dehydrated tomato plants, which was incorporated by immersion alone or in combination with an edible chitosan-based coating in sierra fish fillets. The following treatments were applied: C (Chitosan), TPE (Tomato Plant Extract), TPE-C (TPE-Chitosan), and control (without chitosan and extract). Color, pH, WHC, ATP-related compounds, and K value were monitored during 15 days of storage on ice. Likewise, the total count of mesophiles was determined. The results indicated that treatments C, TPE, and TPE-C were significantly different (p<0.05) from lot control in terms of the concentration of ATP-related compounds, K value, pH, and total mesophilic count. We concluded that application of the extract alone or in combination with chitosan allows for the improvement of the quality and shelf life of the sierra fish fillet.